Millennials' Behavior: Does Stock Investors' Self-Efficacy Mediate Financial Literacy on Financial Behavior? - Arienda Gitty Ramadani; Dewi Khornida Marheni; Hery Haryanto (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Financial literacy among millennials is a fundamental need because many are victims of fraudulent investments. After all, the financial literacy and behavior index is still relatively low. Based on research conducted, almost 86 percent of their financial condition is in the unhealthy category. This novelty perspective sheds light on the influence of both Financial Literacy and Financial Self-Efficacy on this specific group's financial decision-making and behavior. This research is a quantitative type of research with an associative approach. Individual investors participating in The Indonesia Capital Market are the population target in this study. The samples used in this study amounted to 150 models. The sampling technique in this study is purposive sampling. The findings of this study demonstrate a positive relationship between financial literacy and financial self-efficacy. Moreover, the results indicate that financial literacy and self-efficacy significantly impact financial behavior. Furthermore, this study provides evidence supporting the mediating role of financial self-efficacy in the relationship between financial literacy and financial behavior. This conclusion indicates the importance of strengthening financial literacy and self-efficacy in millennial stock investors to encourage positive financial behavior. These steps are expected to help millennial stock investors achieve long-term financial goals better.